Identifying Important Areas for the Release of Five Endemic Species in a Mountainous Landscape: Inference from Spatial Modeling Techniques - Rahman, Dede Aulia; Giri, Misbah Satria; Munawir, Ahmad; Sunderland-Groves, Jacqueline L (Institut Pertanian Bogor (IPB University), 2024)
Efforts to release animals resulting from evacuation and rehabilitation into their natural habitats are important practices in wildlife conservation. Before releasing the animals, it is important to assess the habitat suitability of the areas to support the existence of the animals in the long run. Yet, there is limited study of habitat suitability assessment on national parks as release locations for wild animals. This study aimed to assess the suitable habitat of five charismatic animal species, i.e., Panthera pardus melas, Hylobates moloch, Prinonailurus bengalensis, Nycticebus javanicus, and Nisaetus bartelsi, in Gunung Halimun Salak National Park using Maxent, and to determine potential locations for releasing animal’s species. Models for the P. p. melas show 47,619 ha and 21,391 ha, respectively, suitable as habitat and potential release location, for H. moloch, each is 57,537 ha and 33,471 ha, for P. bengalensis, each is 25,460 ha and 17.189 ha, for N. javanicus, each is 29,848 ha and 15,578 ha, and for N. bartelsi, each is 44,426 ha and 25,660 ha. Our study shows that a suitable habitat can be critical in choosing a wildlife release site. Further consideration of conflict mitigation and practicalities is required to achieve the long-term existence of released species.